“Look at This Great Alice in Wonderland Dress I Found!”: Repairing arguments and hearts with Catherine Hundleby - Linker, Maureen (Informal Logic)

(untitled) (Informal Logic, 2026)
This essay offers a reflective and personal exploration of philosophical friendship, feminist scholarship, and Catherine Hundleby’s transformative work in argumentation theory. Anchored by a metaphysically “magical” road trip to a FEMMSS conference, I trace the evolution of my intellectual and personal bond with Hundleby, sparked by an admiration for Moulton’s groundbreaking article, “A Paradigm of Philosophy: The Adversary Method.” I contextualize our engagement with feminist critiques of adversarial thinking and highlight Hundleby’s advances in argument repair. I also discuss her innovative work with Beverley Anger on the Ad Stuprum fallacy that examines the intersection of sexuality, power, and argumentation. Through personal anecdotes, theoretical insights, and analysis of Hundleby’s TEDX talk, I celebrate her commitment to inclusive, non-adversarial reasoning and feminist mentorship. Ultimately, the essay honors Hundleby’s legacy—her capacity to repair arguments and hearts—as a model for philosophical inquiry and friendship.